2016
DOI: 10.3390/ijms17040571
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Matrix Metalloproteinase 9 Expression as Supporting Marker to Cytokeratin 19 mRNA in Sentinel Lymph Nodes in Breast Cancer Patients

Abstract: One-step nucleic acid amplification (OSNA) detects and quantifies, with the use of a polymerase chain reaction, the presence of cytokeratin 19 mRNA in sentinel lymph nodes. The main advantage of the OSNA assay is the avoidance of second surgery in case of positive sentinel lymph node diagnosis. The objective of this study was to evaluate the significance of matrix metalloproteinase 9 expression by immunohistochemistry as supporting marker to cytokeratin 19 mRNA in sentinel lymph nodes in breast cancer patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Murawski et al assessed the importance of MMP-9 expression as a supporting marker for CK19 mRNA in sentinel lymph nodes in breast cancer patients and the link between this expression and clinical-pathological data. The results indicate a strong correlation of MMP-9 with CK19 mRNA in breast carcinoma [ 13 ]. In turn, Joseph et al indicate an increased level of CK17, which was associated with the increased expression of MMP-9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Murawski et al assessed the importance of MMP-9 expression as a supporting marker for CK19 mRNA in sentinel lymph nodes in breast cancer patients and the link between this expression and clinical-pathological data. The results indicate a strong correlation of MMP-9 with CK19 mRNA in breast carcinoma [ 13 ]. In turn, Joseph et al indicate an increased level of CK17, which was associated with the increased expression of MMP-9.…”
Section: Discussionmentioning
confidence: 99%
“…The common point was indicated in the research on sentinel lymph nodes specimens obtained from breast cancer patients. The study presents the prognostic value of MMP-9 but also its correlation with CK19 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the tumor cells are the ones breaking several tissue barriers with the aim of proliferation and spreading, there is some evidence suggesting that the tumor microenvironment cells, such as stromal cells, support the processes of tumor progression [17][18][19] . The findings suggested that MMPs overexpression might be associated with poor prognosis in breast cancer and its expression is increased with the increase of tumor stage [20][21][22][23] . Appropriate resection of cancer considers macroscopically and microscopically clean margins of specimen.…”
Section: Introductionmentioning
confidence: 95%